The Shell Matters: Self-Organized CdS-ZnS/MnS-Core-Shell-Porphyrin-Polymer Nano-Assemblies for Photocatalysis - Wagner, Maximilian; Gröhn, Franziska (Catalysts, 2022)
A facile synthesis of catalytically tunable core-shell CdS-ZnxMn1-xS-nanoparticles in conjunction with poly(acrylic acid) (PAA) and porphyrin in an aqueous solution is described in the following: The shell composition of the inorganic nanoparticles is varied to tune the optical properties and to optimize the catalytic activity. Further, the tetravalent cationic 5,10,15,20-tetrakis(4-trimethylammoniophenyl) porphyrin (TAPP) fulfills a triple functionality in the catalyst: as a photosensitizer, as an electrostatic linker connecting the nanoparticles and as a probe to investigate the surface composition of the II-VI semiconducting nanoparticles. Different nanoparticles with varying zinc sulfide/manganese sulfide shell ratios are tested with regard to their photocatalytic behavior by crocin bleaching. The results reveal that the shell composition can be a crucial key to optimize the catalytic activity, which can further be important in tuning the reactivity of related systems. Fundamentally, the stepwise multi-component self-assembly in an aqueous solution has been demonstrated to allow the tuning of optic and catalytic properties of core-shell nanoparticles, a general concept that may be widely applicable.
CRIS-Team WoS Importer:2022-09-09